Economic Benefit and Greenhouse Gas Emission Reduction Potential of A Family-Scale Cowdung Anaerobic Biogas Digester - Haryanto, Agus; Cahyani, Dwi; Triyono, Sugeng; Murdapa, Fauzan; Haryono, Dwi (International Journal of Renewable Energy Development, 2017)
The objective of this research was to evaluate economic benefit and greenhouse gas (GHG) emission reduction potential of a family-scale anaerobic cowdung biogas digester. Research was conducted at two villages in Lampung Province, namely Marga Lestari, District of South Lampung and Pesawaran Indah, District of Pesawaran. Economic benefit and GHG emission reduction potential were evaluated from LPG saving due to biogas utilisation for cooking and fertilizer substitution by slurry digestate. Results showed that a family-scale anaerobic cowdung biogas digester demonstrated a good potential to reduce GHG emission, but not in economic. A digester with 4 heads of cow produced biogas at a rate of 1582 L/day. With average methane content of 53.6%, energy value of the biogas was equivalent to 167 kg LPG and able to substitute 52 bottles LPG annually. A family-scale biogas contributed 108.1 USD/year and potentially reduced GHG emission by 5292.5 kg CO2e/year resulted from biomethane potential, LPG, and fertilizer savings.Article History: Received November 15th 2016; Received in revised form January 16th 2017; Accepted February 2nd 2017; Available onlineHow to Cite This Article: Haryanto, A., Cahyani, D., Triyono, S., Murdapa, F., and Haryono, D. (2017) Economic Benefit and Greenhouse Gas Emission Reduction Potential of A Family-Scale Cowdung Anaerobic Biogas Digester. International Journal of Renewable Energy Development 6(1), 29-36.http://dx.doi.org/10.14710/ijred.6.1.29-36